Fear in general populations: a cross-sectional study on perceived fear of common diseases, COVID-19, life events, and environmental threats in 30 countries - Li, Jiaying; Fong, Daniel Yee Tak; Lok, Kris Yuet Wan; Wong, Janet Yuen Ha; Ho, Mandy Man; Choi, Edmond Pui Hang; Pandian, Vinciya; Davidson, Patricia M; Duan, Wenjie; Tarrant, Marie; Lee, Jung Jae; Lin, Chia-Chin; et al. (International Society of Global Health (ISoGH), 2024)
Background: In this study, we assessed the general population's fears towards various diseases and events, aiming to inform public health strategies that balance health-seeking behaviours.